2018
DOI: 10.1007/s00520-018-4137-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in relapsed/refractory multiple myeloma: a systematic review

Abstract: There is paucity of evidence-based data regarding the impact of therapies on quality of life and symptom burden of patients with RRMM. Inclusion of PRO in future studies of patients with RRMM is needed to better inform clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…A recent systematic review revealed a paucity of evidence‐based data describing the impact of therapies on symptoms and quality of life in patients with RRMM, identifying an unmet need to better understand patient burden in this population . Findings from two targeted literature reviews suggested that the total cost of illness in patients with RRMM is driven by treatment choice, as well as symptoms, direct costs, productivity loss, and burden on caregivers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review revealed a paucity of evidence‐based data describing the impact of therapies on symptoms and quality of life in patients with RRMM, identifying an unmet need to better understand patient burden in this population . Findings from two targeted literature reviews suggested that the total cost of illness in patients with RRMM is driven by treatment choice, as well as symptoms, direct costs, productivity loss, and burden on caregivers .…”
Section: Introductionmentioning
confidence: 99%
“…Although direct costs of RRMM have been reported, less is known about patient satisfaction with RRMM therapy, the indirect costs of RRMM, and the impact of disease on caregivers .…”
Section: Introductionmentioning
confidence: 99%
“…QoL is also a central component of health technology and cost-effectiveness assessment [21]. Incorporation of QoL endpoints in clinical trials is therefore essential to allow better clinical decisionmaking in patients with MM [22], including those with relapsed/refractory (RR) MM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study in RRMM patients showed that HRQOL decreased significantly with treatment lines [4]. This evidence is particularly relevant as there is paucity of evidence-based information on PROs in RRMM patients [15].…”
Section: Introductionmentioning
confidence: 99%